Using the kaleidoscope career model to examine generational differences in work attitudes between Gen X and Gen Y– within Malaysia Perspective - Koay, Chee Hua Alwyn (2016)
Generation Y (also known as Yers) has started to take a prominent position in today’s workforce. With this new position comes a new territory of research. The research about this generation has increased over the past years, with most of this research focusing on characteristics of GenY (Sheahan (2005), Martin (2005), Armour (2005)) and the differences between generations (Smola and Sutton (2002), Cennamo and Gardner (2008)). Noticeably, there has been many literature and news (Hoi J., 2013) in which states the difficulty of handling the younger generation specifically the GenY. Though many literatures has been formulated around the difference in the generation, not many literature has been recorded to have study the behaviour of different generation in terms of work values preferences. Hence this research through the utilization of the Kaleidoscope Career Model established by Maniero & Sullivan (2006) is to identify the existence of differences in work values (authenticity, balance and challenge) in different generation in the Malaysian workplace through time-lag method in which study the differences in different point of life in perspective of each individuals. In terms of looking into the different point in life, the measure of authenticity, balance and challenge is used in comparison of the different marital status as well as the education level. This research also includes determining the possibility of different work values in the same generation in different industry, specifically the Engineering and Information Technology industry.